Fluid-Structure Interaction in a 3-by-3 Reduced-Scale Fuel Assembly Network - Guillaume Ricciardi; Sergio Bellizzi; Bruno Collard; Bruno Cochelin (Science and Technology of Nuclear Installations)
We present experimental results on 9 reduced-scale fuel assemblies arranged in a network of 3 by 3, subjected to an axial flow. The objective is to analyse the fluid force induced by the motion of the central fuel assembly on the others fuel assemblies. The displacement of the central fuel assembly is imposed, while the others are fixed. Fluid forces acting on fuel assemblies are measured with force sensors. We observed that the coupling between fuel assemblies increases with the fluid velocity, and that the coupling in the transverse direction is not negligible compared to the coupling in the direction of excitation. We also observe that the fluid flow induces a stiffening of the central fuel assembly.